Edukasi Terhadap Orang Tua dalam Mendampingi Anak Memasuki Sekolah Dasar - Mubarak Ahmad; Muhammad Azhar Nawawi; Ahmad Ruslan; Gery Erlangga (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The lack of understanding possessed by each parent in equipping children in the face of formal education makes parents tend to ignore children's education. So that through this problem, this community service activity was held by holding seminars for parents to prepare their children to enter elementary school. Thus, the purpose of this devotion is to help parents to be responsive in preparing their children to enter the elementary school level after passing through the kindergarten phase. The method used in this service is Participatory Action Reseacrh with the implementation method in the form of a socialization seminar. The results in this community service show that parents need to prepare or make special savings for children's education costs and choose affordable schools both access and finance as well as other supporting aspects in the school environment such as knowledge, skills, and attitudes.